Security information management systems - Andrzejewski, Kamil (Zarządzanie procesem bezpieczeństwa informacji, 2019)
The article includes a literature outline of the scientific field of management sciences concerning issues of security management an organization. The article focuses on identifying literature in this area and describing the process in terms of the essence of management in the organization. The authors who were pioneers of the subject were indicated and the author also pointed to the important roles of the approach to information security management in the process of building and organizational development of the enterprise. At the end of the article, the author discusses opinions of other authors in the selection of the optimal strategy for managing security in an enterprise and shows how it financially a effects the company and its intangible market value
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 4, s. 1-9
Keywords: security management; information; company value; start-up; legal security; IT security; security context; development security management; ERP; fraud; zarządzanie bezpieczeństwem; informacja w organizacji; ocena rynku akcji; nowa wartość rynkowa; bezpieczeństwo prawne; bezpieczeństwo IT; kontekst bezpieczeństwa; zarządzanie bezpieczeństwem ERP; oszustwa